2018
DOI: 10.1001/jamanetworkopen.2018.5220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Factors Associated With Mortality in First-Episode Infective Endocarditis Among Persons Who Inject Drugs

Abstract: Key Points Question In first-episode infective endocarditis in persons who inject drugs, what are the clinical differences between patients who receive surgery vs those who are medically treated, and which factors are associated with mortality? Findings In this case series of 370 first-episode cases of infective endocarditis, the main significant differences between persons who inject drugs who received surgery and those who did not were the site of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 59 publications
4
107
1
3
Order By: Relevance
“…Other predictors of inpatient mortality described in our report included patients older than 40 years of age, severe sepsis or shock on presentation; these predictors are similar to previously described literature emphasizing the importance of initial presentation with multiorgan dysfunction and risk of systemic embolization [15][16][17][18][19][20]. In a study by Ferrera et al, IE patients presenting with atrial fibrillation had higher in-hospital mortality independently from other relevant clinical variables [21].…”
Section: Discussionsupporting
confidence: 87%
“…Other predictors of inpatient mortality described in our report included patients older than 40 years of age, severe sepsis or shock on presentation; these predictors are similar to previously described literature emphasizing the importance of initial presentation with multiorgan dysfunction and risk of systemic embolization [15][16][17][18][19][20]. In a study by Ferrera et al, IE patients presenting with atrial fibrillation had higher in-hospital mortality independently from other relevant clinical variables [21].…”
Section: Discussionsupporting
confidence: 87%
“…8,13,17 Opioid agonist therapy (buprenorphine and methadone) to prevent withdrawal should be routinely offered to all patients with OUD including those with infectious complications of OUD to facilitate appropriate medical treatment and engage patients in long-term addiction treatment. Referral to addiction treatment has been associated with improved IDU-associated endocarditis mortality, 18 and initiation of medications for OUD (MOUD) can be achieved successfully in the emergency department, inpatient wards, and specifically in patients admitted with IDU-associated endocarditis. [19][20][21] Protocols and resources for inpatient management of withdrawal and…”
Section: Key Management Questions In the Inpatient Management Of Infementioning
confidence: 99%
“…In contrast, another study found that surgery was the strongest predictor of survival among patients with IDU-associated endocarditis after a median of 3.6 years follow-up. 18 Another consideration is that patients with IDU-associated infection tend to be younger, and despite advancements, many modern prostheses have a finite lifespan. When multiple surgical options exist, a procedure that avoids prosthetic material is preferred.…”
Section: Is Surgical Placement Of Prosthetic Materials Safe In Patientmentioning
confidence: 99%
“…There has been a rising incidence of infective endocarditis (IE) among people who inject drugs (PWID), paralleling the opioid epidemic in North America (1)(2)(3)(4)(5)(6). This infectious complication of intravenous drug use (IVDU) is associated with significant morbidity and mortality requiring extensive and costly(1,2) multidisciplinary care (7). PWID are at risk of IE due to: comorbidities of HIV, hepatitis C and skin and soft tissue infections; non-sterile injection practices; and the reuse of injection drug preparation equipment (IDPE) (2,4,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the components of hydromorphone-CR capsules that provide the controlled release, increase survival of HIV (19) and Staphylococcus aureus (12), which cause the vast majority of IE cases (7). Moreover, residual drug remains in cookers and filters after an initial injection, allowing PWID to resolubilize the remaining drug and conduct multiple injections (11,14,16,19,20) (Fig.…”
Section: Introductionmentioning
confidence: 99%